If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -5x + 1 = 3x + 2 Reorder the terms: 9 + 1 + -5x = 3x + 2 Combine like terms: 9 + 1 = 10 10 + -5x = 3x + 2 Reorder the terms: 10 + -5x = 2 + 3x Solving 10 + -5x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 10 + -5x + -3x = 2 + 3x + -3x Combine like terms: -5x + -3x = -8x 10 + -8x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 10 + -8x = 2 + 0 10 + -8x = 2 Add '-10' to each side of the equation. 10 + -10 + -8x = 2 + -10 Combine like terms: 10 + -10 = 0 0 + -8x = 2 + -10 -8x = 2 + -10 Combine like terms: 2 + -10 = -8 -8x = -8 Divide each side by '-8'. x = 1 Simplifying x = 1
| 8(a+3)=57.6 | | r^2+9t+8= | | -0.2=4c-3 | | (a+5)c= | | -9.12/1.6 | | 7e-9=-2 | | p^3-p^2+p-1=0 | | 1/2(x-3)=5/12+2/3(2x-5) | | 9p=66.6 | | [8-9]+15-16/14(-1)= | | ax-4cx+5ay-20cy=0 | | 7(8+x)= | | 9(a+5)=117 | | 5(6-.10)=3(6) | | 81=5/9(f-32) | | (15/7)p=-3 | | 15x^3-12x^2+35x-28= | | -2x^2+84x-441=0 | | 15x-36-x^2=0 | | 5e-4=26 | | 7x+5=3.5x+11 | | 5+10r-2=9r+51-7r | | (-2*1/7)p=-3 | | 7+9n=7n+5 | | 16.5-0.5x=3(2.5x+3) | | 7x+y=4fory | | 3m+12m=75 | | 6x=2*1-4 | | (x/x-2)-2=6/x-2 | | 4p=-44+2p | | 2x-42.6=90 | | z/19=-27 |